Preparation method of liquid zirconium oxide for 3D printing

By preparing liquid zirconia ink for 3D printing, the problems of poor antibacterial properties and plaque formation on the denture surface are solved, and higher antibacterial properties and biological activity are achieved, and the service life of the denture is extended.

CN119462134AInactive Publication Date: 2025-02-18THALES MEDICAL IND (SHENZHEN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411340815.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing denture manufacturing technology, the poor antibacterial properties of the material and the surface roughness are difficult to maintain consistency, resulting in the formation of plaque and the decalcification of enamel.

Method used

Using a liquid zirconia preparation method for 3D printing, the particle size is 50 to 50 by mixing silica, calcium oxide, potassium oxide and phosphorus pentoxide in a specific proportion and processing it through a preset temperature program. 100nm zirconia nanoparticles. Then, these nanoparticles were mixed with calcium phosphosilicate sodium nanoparticles, organic solvents, dispersants, binders and surfactants, adjusted pH, and filtered through a 3-micron butterfly spray-painted filter to obtain a 3D printed model ink.

Benefits of technology

Through the prepared liquid zirconia ink, the surface of the 3D printed denture has stronger antibacterial properties and biological activity, which can reduce bacterial adhesion and plaque formation, and improve the hygiene and service life of the denture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462134A_ABST
    Figure CN119462134A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of liquid zirconium oxide for 3D printing, which comprises the following steps: mixing silicon dioxide, calcium oxide, potassium oxide and phosphorus pentoxide according to a weight ratio of 42: 20: 15: 5, and treating through a preset temperature program to obtain zirconium oxide nanoparticles with the particle size of 50-100nm; the preparation method comprises the following steps: mixing 40%-60% by mass of zirconium oxide nanoparticles, 5%-8% by mass of sodium calcium phosphate silicate nanoparticles, 30%-60% by mass of an organic solvent and 0.1%-0.3% by mass of a dispersing agent, and uniformly stirring in a stirrer; in the stirring process, 0.1%-3% of a binder and 1%-2% of a surfactant are added into the stirrer to continue to be stirred evenly, then a pH regulator is added to adjust the pH value to 7-8, a 3-micron butterfly inkjet filter is adopted for filtering, and the 3D printing model ink is obtained. According to the invention, the formation of dental plaque of the false tooth can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of computer technology, and in particular to a method for preparing liquid zirconium oxide for 3D printing. Background Art

[0002] Existing denture manufacturing technologies, whether traditional manual techniques or computer numerical control (CNC) processing technologies, have certain limitations and defects. Whether it is handmade or CNC-processed dentures, due to the poor antibacterial properties of the material itself and the difficulty in maintaining consistent surface roughness for a long time during processing, the roughness of the material surface will increase during the manufacturing process, which provides favorable conditions for the adsorption and reproduction of bacteria. In addition, the increase in the roughness of the material surface may cause tiny gaps between the dentures and the abutment teeth. These gaps are easy to become places for bacteria to breed, which in turn causes the accumulation of dental plaque and decalcification of enamel.

[0003] Although 3D printing technology has shown great potential in denture manufacturing, dental dentures made with it still face challenges in actual wearing. In the patient's oral environment, salivary proteins or glycoproteins are easily adsorbed to the denture surface and form a thin film, which can promote bacterial adhesion, colonization and aggregation, and ultimately accelerate the formation of dental plaque. In addition, the restoration is not tightly combined with the tooth surface, which easily forms a gap between the two, further providing space for bacteria to grow, thereby damaging the integrity of the restoration.

[0004] From the above, it can be seen that the problem of how to reduce the formation of denture plaque still needs to be solved. Summary of the invention

[0005] The present application provides a method for preparing liquid zirconium oxide for 3D printing, which can solve the problem of how to reduce the formation of dental plaque in the related art. The technical solution is as follows:

[0006] According to one aspect of the present application, a method for preparing liquid zirconium oxide for 3D printing includes: mixing silicon dioxide, calcium oxide, potassium oxide and phosphorus pentoxide in a weight ratio of 42:20:15:5 and treating the mixture through a preset temperature program to obtain zirconium oxide nanoparticles with a particle size of 50 to 100 nm; mixing zirconium oxide nanoparticles with a mass ratio of 40% to 60%, sodium calcium phosphosilicate nanoparticles with a mass ratio of 5% to 8%, 30% to 60% of an organic solvent, and 0.1% to 0.3% of a dispersant, and putting the mixture into a blender and stirring evenly; during the stirring process, adding 0.1% to 3% of a binder and 1% to 2% of a surfactant to the blender and continuing to stir evenly, then adding a pH adjuster to adjust the pH value to 7 to 8, and filtering with a 3-micron butterfly inkjet filter to obtain 3D printing model ink.

[0007] In an exemplary embodiment, in the process of being processed by a preset temperature program, the specific heating process in the heating furnace includes: heating from room temperature to 100°C, a heating rate of 4°C / min, and a holding time of 60 minutes; heating from 100°C to 450°C, a heating rate of 4°C / min, and a holding time of 120 minutes; heating from 450°C to 800°C, a heating rate of 4°C / min, and a holding time of 120 minutes; heating from 900°C to 1450°C, a heating rate of 10°C / min, and a holding time of 100 minutes, so that the raw materials are melted at 1450°C to form a uniform mixture.

[0008] In an exemplary embodiment, in the process of obtaining zirconium oxide nanoparticles with a particle size of 50 to 100 nm, after obtaining the corresponding mixture, the method also includes: cooling the heating furnace by water cooling, when the temperature in the furnace drops to 300°C, opening the furnace for air cooling for 30 minutes, then taking out the mixture in the furnace and putting it into room temperature pure water with a conductivity of 0 to quickly cool the mixture; first taking out the mixture from the water after cooling and putting it into a drying oven for drying, the drying temperature is 100°C, and the drying time is 60 minutes; then crushing and grinding the dried mixture, and sieving the mixture with a 1200-mesh sieve, wherein the sieved particles are screened using flow cytometry to obtain sodium calcium phosphosilicate particles with a particle size of 50 to 100 nm.

[0009] In an exemplary embodiment, the method further includes: the organic solvent is selected from one or more of ethylene glycol, propylene glycol, butylene glycol, polyethylene glycol, ethylene glycol monobutyl ether, isopropanol, n-propanol, and ethylene glycol dimethyl ether; and the dispersant is selected from one or more of anionic carboxylic acid group polymers, ammonium polyacrylate, and sodium polyacrylate.

[0010] In an exemplary embodiment, the method further includes: the binder is selected from one or more of polyvinyl alcohol, polyvinyl butyral, epoxy resin, phenolic resin, acrylamide, polyacrylic resin, and polyvinyl acetate; the surfactant is selected from one of hydroxyl levulinate, DTAB, CTAB, dodecylaminoacetic acid, and hexadecyltriethylenediaminetetraacetic acid.

[0011] According to one aspect of the present application, a denture manufacturing method based on 3D printing uses a 3D printing model ink prepared by a method as described in a method for preparing liquid zirconium oxide for 3D printing. The method also includes: using an inkjet 3D printer to control the nozzle to spray 3D printing model ink and support material ink according to data generated by slicing software, and printing tooth parts layer by layer; after printing is completed, the print tray is cooled to 60°C, and then the print is taken out for post-processing, including removing the support material and sintering.

[0012] In an exemplary embodiment, the method also includes: the specific process parameters of the 3D printing are: a printing speed of 1 min / layer, a thickness of each layer of 2 to 10 μm, 24 groups of nozzles, 12 groups of nozzles spray support material ink, and 12 groups of nozzles spray 3D printing model ink of parts. When printing each layer, the nozzle group that sprays the support material ink and the nozzle group that sprays the 3D printing model ink of the parts simultaneously spray corresponding inks, so that each layer of the denture is formed in one go.

[0013] In an exemplary embodiment, the method further includes: the supporting material ink is composed of nano sodium carbonate particles, an auxiliary solvent, and a dispersant, wherein the nano sodium carbonate particles have a particle size of 50 to 100 nm and a content of 40 to 60 wt%.

[0014] The technical solution provided in the present application has the following beneficial effects: by preparing zirconium oxide nanoparticles with a particle size of 50 to 100 nm, these nanoparticles have a larger surface area to volume ratio, which gives them stronger antibacterial properties; at the same time, by adding sodium calcium phosphosilicate nanoparticles, these particles can release ions through hydrolysis reaction in the oral environment to form hydroxyapatite, promote the remineralization of teeth, and these ions can inhibit the growth of bacteria; in addition, by adding sodium calcium phosphosilicate nanoparticles to the ink, these nanoparticles are distributed on the surface of the printed denture, and they can react with the liquid in the mouth to form a protective film, which can reduce the adhesion of bacteria and thus reduce the formation of dental plaque. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0016] Figure 1 is a flow chart of a method for preparing liquid zirconium oxide for 3D printing according to an exemplary embodiment;

[0017] Figure 2 It is a flow chart of a denture manufacturing method based on 3D printing according to an exemplary embodiment. DETAILED DESCRIPTION

[0018] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be interpreted as limiting the present application.

[0019] It will be understood by those skilled in the art that, unless expressly stated, the singular forms "one", "said", and "the" used herein may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present disclosure refers to the presence of the features, integers, steps, operations, elements, and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof. It should be understood that when we refer to an element as being "connected" or "coupled" to another element, it may be directly connected or coupled to the other element, or there may be intermediate elements. In addition, the "connection" or "coupling" used herein may include wireless connection or wireless coupling. The term "and / or" used herein includes all or any unit and all combinations of one or more associated listed items.

[0020] In order to make the objectives, technical solutions and advantages of the present application clearer, the implementation methods of the present application will be further described in detail below with reference to the accompanying drawings.

[0021] This application embodiment provides a method for preparing liquid zirconium oxide for 3D printing, please refer to Figure 1 , the method may include the following steps:

[0022] S100, silicon dioxide, calcium oxide, potassium oxide and phosphorus pentoxide are mixed in a weight ratio of 42:20:15:5 and then treated through a preset temperature program to obtain zirconium oxide nanoparticles with a particle size of 50 to 100 nm.

[0023] Among them, it should be pointed out that in the process of being treated by a preset temperature program, all the mixed chemical raw materials are placed in a heating furnace for heating, and the temperature in the heating furnace is different in different time periods. The specific process is: heating from room temperature to 100°C, a heating rate of 4°C / min, and a holding time of 60min; heating from 100°C to 450°C, a heating rate of 4°C / min, and a holding time of 120min; heating from 450°C to 800°C, a heating rate of 4°C / min, and a holding time of 120min; heating from 900°C to 1450°C, a heating rate of 10°C / min, and a holding time of 100min, so that the raw materials melt at 1450°C to form a uniform mixture.

[0024] After obtaining the corresponding mixture, it is necessary to obtain the corresponding sodium calcium phosphosilicate particles. The specific process includes:

[0025] S101, the heating furnace is cooled by water cooling. When the temperature in the furnace drops to 300°C, the furnace is opened for air cooling for 30 minutes, and then the mixture in the furnace is taken out and placed in pure water at room temperature with a conductivity of 0 to quickly cool the mixture.

[0026] Among them, water cooling can quickly reduce the temperature inside the heating furnace, prevent the material from overheating and causing changes in physical or chemical properties, and ensure the structural stability of the material and the predetermined physical properties; the second furnace air cooling is to further reduce the temperature inside the furnace and allow the material to cool slowly, which helps to maintain the uniformity of the internal structure of the material and reduce stress concentration caused by rapid cooling; finally, rapid cooling helps to fix the microstructure of the material and avoid crystal growth caused by slow cooling, thereby ensuring that the final material has the required nano-scale particle size.

[0027] S102, after cooling, the mixture is taken out from the water and placed in a drying oven for drying at a temperature of 100° C. for a drying time of 60 min.

[0028] The drying process is to remove residual moisture from the material to avoid the introduction of unnecessary impurities during subsequent grinding and preparation, while also helping to maintain the stability of the material.

[0029] S103, crushing and grinding the dried mixture, and sieving the mixture with a 1200-mesh sieve, wherein the sieved particles are screened by flow cytometry to obtain sodium calcium phosphosilicate particles with a particle size of 50 to 100 nm.

[0030] It should be pointed out here that grinding can further refine the material particles, making it easier to screen in the future, and also helps to improve the uniformity of the material. The ground material is screened with a 1200 mesh screen to remove oversized or unqualified particles, ensuring that all particles are of the same size and meet the needs of subsequent processes.

[0031] In addition, flow cytometry is used to screen the sieved particles to obtain sodium calcium phosphosilicate particles with a particle size of 50 to 100 nm. Flow cytometry detects the scattered light signals generated by the particles under laser irradiation in a flowing state, and uses electric fields or magnetic fields to separate the target particles according to different signals, thereby obtaining nano-scale particles that meet the requirements.

[0032] By executing steps S101 to S103, sodium calcium phosphosilicate nanoparticles with a particle size of 50 to 100 nm can be prepared. These nanoparticles have good biological activity and can release ions through hydrolysis in the oral environment, inhibit bacterial growth, reduce the aggregation of dental plaque, and improve the biological activity and biocompatibility of dentures. At the same time, through strict temperature control and cooling process, the structural stability and predetermined physical properties of the material are ensured, which provides a basis for the subsequent 3D printing to prepare high-quality liquid zirconium oxide model ink.

[0033] S110, 40% to 60% by mass of zirconium oxide nanoparticles, 5% to 8% by mass of sodium calcium phosphosilicate nanoparticles, 30% to 60% by mass of an organic solvent, and 0.1% to 0.3% by mass of a dispersant are mixed, and the mixture is put into a mixer and stirred evenly.

[0034] Among them, by mixing zirconium oxide nanoparticles and sodium calcium phosphosilicate nanoparticles, combining organic solvents, dispersants, and binders, a stable ink system is formed to ensure that the ink has good fluidity and uniformity during the 3D printing process.

[0035] S120, during the stirring process, 0.1% to 3% of a binder and 1% to 2% of a surfactant are added to the mixer and the stirring is continued to be uniform, and then a pH adjuster is added to adjust the pH value to 7 to 8, and the mixture is filtered through a 3-micron butterfly inkjet filter to obtain a 3D printing model ink.

[0036] Among them, binders and surfactants are added to form a stable ink system to ensure that the ink has good fluidity and uniformity during the 3D printing process; pH adjusters are added to keep the pH value of the ink within an appropriate range, which is conducive to maintaining the stability of the ink and extending its shelf life; and larger particles that may exist are filtered out to ensure that the ink is pure and free of impurities, making it suitable for 3D printing.

[0037] In the embodiment of the present application, the organic solvent is selected from one or more of ethylene glycol, propylene glycol, butylene glycol, polyethylene glycol, ethylene glycol monobutyl ether, isopropyl alcohol, n-propyl alcohol, and ethylene glycol dimethyl ether; the organic solvent plays a role in dissolving other components (such as nanoparticles, binders, surfactants, etc.) in the 3D printing liquid zirconium oxide ink, ensuring that these components are evenly dispersed in the ink, while controlling the viscosity of the ink for 3D printing. Suitable organic solvents can improve the fluidity and stability of the ink and ensure the smooth progress of the printing process.

[0038] In the embodiment of the present application, the dispersant is selected from one or more of anionic carboxylic acid group polymers, ammonium polyacrylate, and sodium polyacrylate; the main function of the dispersant is to prevent the nanoparticles from agglomerating in the ink and ensure that the nanoparticles can be evenly dispersed in the organic solvent. By using a dispersant, the stability of the ink can be improved, and the sedimentation of nanoparticles during long-term storage or printing can be avoided, thereby ensuring the consistency of printing quality. The dispersant can also maintain the suspension of nanoparticles through electrostatic repulsion or other mechanisms.

[0039] In an embodiment of the present application, the binder is selected from one or more of polyvinyl alcohol, polyvinyl butyral, epoxy resin, phenolic resin, acrylamide, polyacrylic resin, and polyvinyl acetate; the binder plays a role in connecting the nanoparticles during the printing process, enhancing the mechanical strength and stability of the printed object. The binder can help the nanoparticles form a strong bond, so that the printed tooth parts have sufficient hardness and toughness, and are not easy to break or wear. In addition, the binder can also promote the bonding between the particles during the sintering process, further improving the overall performance of the material.

[0040] In an embodiment of the present application, the surfactant is selected from one of hydroxylevulinate, DTAB, CTAB, dodecanedioic acid, and hexadecyltriethylenediaminetetraacetic acid (TEDA); the surfactant can reduce the surface tension of the ink, improve the wettability of the ink, and enable the ink to better adhere to the printing platform and spread more easily during the printing process. The surfactant also helps to control the formation and ejection behavior of ink droplets to ensure printing accuracy. In addition, the surfactant can also prevent the aggregation of nanoparticles in the ink, further improving the print quality. By using a surfactant, it is possible to ensure that the ink forms uniform droplets during the ejection process.

[0041] Compared with related technologies, the liquid zirconium oxide ink prepared by the above method can reduce the formation of dental plaque in the following aspects when used for 3D printing dentures:

[0042] 1. Sodium calcium phosphosilicate nanoparticles release ions through hydrolysis in the oral environment. These ions can promote tooth remineralization and inhibit bacterial growth. In addition, nano-scale particles provide a larger surface area to volume ratio, which enhances the antibacterial properties of the material and reduces the adhesion and aggregation of bacteria on the denture surface.

[0043] 2. Through 3D printing technology, high-precision printing can be achieved to ensure a smooth surface of the denture, reducing the chance of bacterial adhesion; in addition, the smooth surface reduces the adsorption of bacteria and proteins, reducing the possibility of plaque formation.

[0044] 3. The presence of sodium calcium phosphosilicate nanoparticles improves the bioactivity and biocompatibility of the material, promotes tissue regeneration, and reduces the occurrence of inflammation; in addition, the improved biocompatibility means that the material is less likely to cause an immune response, thereby reducing the chance of bacterial colonization.

[0045] 4. By precisely adjusting the ratio of zirconium oxide nanoparticles, sodium calcium phosphosilicate nanoparticles, organic solvents, dispersants, binders and surfactants, the surface of the printed denture is evenly distributed with antibacterial components, which improves the overall performance of the material.

[0046] In summary, the liquid zirconia ink prepared by the above method, combined with 3D printing technology, can effectively reduce bacterial adhesion and plaque formation on the surface of dentures, thereby improving the hygiene and service life of dentures.

[0047] The present application provides a method for manufacturing a denture based on 3D printing. Figure 2 , the method comprises the following steps:

[0048] S200 uses an inkjet 3D printer to control the nozzle to spray 3D printing model ink and support material ink according to the data generated by the slicing software, and print tooth parts layer by layer.

[0049] Among them, the 3D printing model ink is prepared using the aforementioned method, that is, by precisely controlling the proportions of zirconium oxide nanoparticles, sodium calcium phosphosilicate nanoparticles, organic solvents, dispersants, binders, surfactants and pH adjusters, and obtaining pure 3D printing model ink by filtration, which can ensure that the printed tooth parts have good biocompatibility, antibacterial properties and surface smoothness, and reduce the accumulation of dental plaque.

[0050] Among them, it should be pointed out here that the supporting material ink is composed of nano sodium carbonate particles, auxiliary solvents, and dispersants, wherein the nano sodium carbonate particles have a particle size of 50 to 100 nm and a content of 40 to 60 WT%, and the auxiliary solvent is mainly a mixture of ethylene glycol ethers; the supporting material ink provides temporary support for the tooth parts during the printing process to ensure that the parts will not be deformed during the molding process.

[0051] In the embodiment of the present application, the specific process parameters of 3D printing are: printing speed 1min / layer, thickness of each layer is 2 to 10μm, there are 24 groups of nozzles, of which 12 groups of nozzles spray support material ink, and 12 groups of nozzles spray 3D printing model ink of parts. When printing each layer, the nozzle group that sprays support material ink and the nozzle group that sprays 3D printing model ink of parts simultaneously spray corresponding inks, so that each layer of the denture can be formed in one go.

[0052] It should be pointed out here that high-precision printing parameters ensure the detail restoration of tooth parts, reduce the time for doctors to adjust the mold later, and improve production efficiency; in addition, by precisely controlling the type and position of ink sprayed by the nozzle, tooth parts are built layer by layer to ensure the dimensional accuracy and surface quality of the final product.

[0053] S210, after printing is completed, the printing tray is cooled to 60°C, and then the printed part is taken out for post-processing, including removing support materials and sintering.

[0054] Cool the printing tray to 60°C and take out the printed parts after lowering the temperature appropriately. This can avoid deformation of parts due to excessive temperature and facilitate subsequent processing.

[0055] Among them, removing support materials: removing the materials used for support during the printing process by physical or chemical methods; sintering molding: subjecting the printed parts to high-temperature treatment to further strengthen the structure of the material and improve its mechanical strength; it should be pointed out that removing support materials ensures the integrity and aesthetics of the final product; the sintering process improves the mechanical properties of dental parts, making them more suitable for practical use.

[0056] In summary, high-precision 3D printing technology ensures the dimensional accuracy and surface quality of dental parts, reduces the time for doctors to adjust molds in the later stage, and improves production efficiency. The layer-by-layer printing technology ensures the accuracy of each layer and reduces the surface roughness caused by material accumulation. The liquid zirconia ink prepared by the above method, combined with 3D printing technology, can effectively reduce bacterial adhesion and plaque formation on the surface of dentures, thereby improving the hygiene and service life of dentures.

[0057] It should be understood that, although the steps in the flowchart of the accompanying drawings are displayed in sequence as indicated by the arrows, these steps are not necessarily executed in sequence in the order indicated by the arrows. Unless otherwise specified herein, there is no strict order restriction on the execution of these steps, and they can be executed in other orders. Moreover, at least a part of the steps in the flowchart of the accompanying drawings may include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn or alternately with other steps or at least a part of the sub-steps or stages of other steps.

[0058] The above description is only a partial implementation method of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application. These improvements and modifications should also be regarded as the scope of protection of the present application.

Claims

1. A method for preparing liquid zirconium oxide for 3D printing, characterized in that: include: Silicon dioxide, calcium oxide, potassium oxide and phosphorus pentoxide are mixed in a weight ratio of 42:20:15:5 and then treated with a preset temperature program to obtain zirconium oxide nanoparticles with a particle size of 50 to 100 nm; Mix 40% to 60% by mass of zirconium oxide nanoparticles, 5% to 8% by mass of sodium calcium phosphosilicate nanoparticles, 30% to 60% by mass of an organic solvent, and 0.1% to 0.3% by mass of a dispersant, and mix them in a blender to mix them evenly; During the stirring process, add 0.1% to 3% of the binder and 1% to 2% of the surfactant into the mixer and continue to stir evenly. Then add the pH adjuster to adjust the pH value to 7 to 8, and filter with a 3-micron butterfly inkjet filter to obtain 3D printing model ink.

2. The method according to claim 1, characterized in that In the process of being processed by the preset temperature program, the specific heating process in the heating furnace includes: Heat from room temperature to 100°C, with a heating rate of 4°C / min and a holding time of 60 min; heat from 100°C to 450°C, with a heating rate of 4°C / min and a holding time of 120 min; heat from 450°C to 800°C, with a heating rate of 4°C / min and a holding time of 120 min; heat from 900°C to 1450°C, with a heating rate of 10°C / min and a holding time of 100 min, so that the raw materials melt at 1450°C to form a uniform mixture.

3. The method according to claim 2, characterized in that In the process of obtaining zirconium oxide nanoparticles with a particle size of 50 to 100 nm, after obtaining the corresponding mixture, the method further comprises: The heating furnace is cooled by water. When the temperature in the furnace drops to 300°C, the furnace is opened for air cooling for 30 minutes. Then the mixture in the furnace is taken out and placed in pure water at room temperature with a conductivity of 0 to cool the mixture quickly. After cooling, the mixture is taken out of the water and placed in a drying oven for drying at a temperature of 100°C for 60 minutes. The dried mixture is then crushed and ground, and the mixture is sieved with a 1200-mesh sieve, wherein the sieved particles are screened using flow cytometry to obtain sodium calcium phosphosilicate particles with a particle size of 50 to 100 nm.

4. The method according to claim 1, characterized in that The method also includes: The organic solvent is selected from one or more of ethylene glycol, propylene glycol, butylene glycol, polyethylene glycol, ethylene glycol monobutyl ether, isopropanol, n-propanol, and ethylene glycol dimethyl ether; The dispersant is selected from one or more of anionic carboxylic acid group polymers, ammonium polyacrylate, and sodium polyacrylate.

5. The method according to claim 1, characterized in that The method also includes: The binder is selected from one or more of polyvinyl alcohol, polyvinyl butyral, epoxy resin, phenolic resin, acrylamide, polyacrylic acid resin, and polyvinyl acetate; The surfactant is selected from one of hydroxylevulinate, DTAB, CTAB, dodecyltriethylenediaminetetraacetic acid and hexadecyltriethylenediaminetetraacetic acid.

6. A method for manufacturing dentures based on 3D printing, characterized in that: A 3D printing model ink prepared using the method as claimed in any one of claims 1 to 5, the method further comprising: Use an inkjet 3D printer to control the nozzle to spray 3D printing model ink and support material ink according to the data generated by the slicing software, and print the tooth parts layer by layer; After printing is completed, the printing tray is cooled to 60°C, and the printed part is then taken out for post-processing, including removing support materials and sintering.

7. The method according to claim 6, characterized in that The method also includes: The specific process parameters of the 3D printing are: printing speed 1min / layer, thickness of each layer is 2 to 10μm, there are 24 groups of nozzles, of which 12 groups of nozzles spray support material ink, and 12 groups of nozzles spray 3D printing model ink of parts. When printing each layer, the nozzle group that sprays support material ink and the nozzle group that sprays 3D printing model ink of parts simultaneously spray corresponding inks, so that each layer of the denture can be formed in one go.

8. The method according to claim 6, characterized in that The method also includes: The supporting material ink is composed of nano sodium carbonate particles, auxiliary solvents and dispersants, wherein the nano sodium carbonate particles have a particle size of 50 to 100 nm and a content of 40 to 60 wt%.

Citation Information

Patent Citations

  • 3-d printing of porous implants

    CN108724712A

  • Composition for resisting tooth sensitivity, preparation method and application thereof, and oral care product containing composition

    CN113908067A